Practical aspects of using the information and search system «Pollen of plants growing in the Republic of Belarus», in forensics and ecology - Pazniak, Sergei S.; Khokh, Anna N.; Tonkonogov, Boris A. (Journal of the Belarusian State University. Ecology, 2020)
The source data for the creation of a reference information-search system «Pollen of woody, shrubby and herbaceous plants growing in the Republic of Belarus» were digital images of the main taxa of plants. Using a MIKMED 6 light binocular biological microscope (LOMO-Microsystems) with magnification of x40, the external structure of pollen grains of 32 taxons of scientific and forensic interest was studied, their digital images were obtained. 50 herbarium and 40 native specimens of woody, shrubby and herbaceous plants were studied. A subsystem of user tools and front-end tools, database generation and testing has been developed, which represents various software units and objects (procedures, functions, modules and forms).Testing of the developed reference and information retrieval system confirmed its efficiency in solving individual problems in the field of forensic science – the selection of the most likely taxonomic groups of plants and the comparison of pollen grains found in the studied sample with the images and reference drugs available in the database, and also in the field of ecology – the identification of teratomorphic pollen grains, indicating the state of the environment, by comparing the experimentally obtained morphological structure of pollen grains with the existing normal characteristics in the «Information System for the Identification of Plant Objects Based on Carpological, Palynological and Anatomical Data» of Moscow State University.
Keywords: pollen grains; taxonomic composition; reference information retrieval system; database management system; functional structure, algorithms, interface